Corruption and internet governance. Issue 2 (2014) - Ewan Sutherland
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to review the extent and the manner in which internet governance systems could and do engage with the problems of potential and actual corruption.Design/methodology/approach – A review of internet multistakeholder systems and their compatibility with global best practice in countering corruption.Findings – The multistakeholder systems contain systemic weaknesses, exposing them to risks of corruption and capture that would be very difficult to identify and eradicate.Practical implications – A number of opportunities are identified to improve resilience of internet multistakeholder systems against the dangers of capture and corruption.Originality/value – There is no research published on this topic. <ack> <x xml:space="preserve"> Acknowledgements </x> Received 20 May 2013 Revised 30 September 2013 1 November 2013 Accepted 28 November 2013 The author is grateful to the participants at the Giga‐Net Workshop in Geneva, in May 2013 and to Jason Whalley (University of Northumbria) and Bryan Clark (University of Strathclyde). </ack>